Role of nonsurgical periodontal therapy on leptin levels and total antioxidant capacity in chronic generalised periodontitis patients - A clinical trial - Swet Nisha; Avinash Bettahalli Shivamallu; Akila Prashant; Manish Kumar Yadav; Sheela Kumar Gujjari; Pratibha Shashikumar (Elsevier, 2022)
Introduction: Periodontitis causes oxidative stress and reduce total antioxidant levels. The aim of this study was to determine the effect of non-surgical periodontal treatment on leptin levels and total antioxidant capacity in chronic periodontitis. Materials and methods: A total of 35 chronic periodontitis (ChP) patients and 35 systemically and periodontal healthy subjects were enrolled in this study. Further, the ChP group received nonsurgical periodontal therapy (NSPT). Leptin and total antioxidant capacity (TAOC) was measured in serum and saliva samples at baseline, 3 months and 6 months after non-surgical periodontal therapy. Clinical parameters measured were measured at baseline, 1, 3 and 6 months interval. Results: The mean serum leptin and TAOC levels in control group were significantly higher compared to chronic periodontitis group (p < 0.05). The control group had lower mean salivary leptin levels and higher mean salivary TAOC levels as compared to periodontitis group(p < 0.05). Clinical parameters were improved in ChP group post therapy (p < 0.05). However, the periodontal treatment showed insignificant changes in serum and salivary leptin and TAOC levels. Conclusion: Chronic periodontitis is significantly associated with serum and salivary TAOC and leptin levels. Non surgical periodontal therapy didn't alter the local and systemic TAOC and leptin levels.